Minhaj Beragama Seorang Muslim dalam Al-Qur’an - Nurhidayah, Lilik; Albani, Fadel Fahmi (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
Studying, understanding and practicing Islam correctly is the primary need of every Muslim. In this case, a Muslim must follow the methods and rules that Allah has blessed. In this study, the problem that the author examines is the verses of the Qur'an related to the religious minhaj of a Muslim in the Qur'an and how it is interpreted and how the religious minhaj of a Muslim is in the Qur'an. This study aims to explain the verses of the Qur'an related to the religious minhaj of a Muslim and their interpretation and explain the religious minhaj of a Muslim in the Qur'an. This study uses the method of literature review (library research). This method is a method that discusses an idea in the Qur'an that is not stated explicitly but substantially the idea is contained in the Qur'an. The conclusion of this study shows that the Qur'an has explained how the religious minhaj is a Muslim. The sources in taking the Muslim minhaj are the Qur'an and the Sunnah with the reasoning of the as-salafuṣ aṣ-ṣâliḥ raḍiyallahu 'anhum. The religious minhaj of a Muslim includes always asking for guidance from Allah ta'âlâ, following in the footsteps of the as-salafuṣ aṣ-ṣâliḥ raḍiyallahu 'anhum, enjoining makruf nahi munkar, not following the path of misguidance and not dividing, always repenting and returning to Allah ta'âlâ, being hostile to people -people who are hostile to Islam, love each other, love and care for fellow Muslims, maintain the quality and quantity of muamalah with Allah ta'âlâ.